Biomechanical Testing of Suture Anchor Versus Transosseous Tunnel Technique for Quadriceps Tendon Repair Yields Similar Outcomes: A Systematic Review - John W. Belk, B.A; Adam Lindsay, M.D; Darby A. Houck, B.A; Jason L. Dragoo, M.D; James W. Genuario, M.D; Stephanie W. Mayer, M.D; Rachel M. Frank, M.D; Eric C. McCarty, M.D (Elsevier, 2021)
Purpose: To systematically review the literature to evaluate the biomechanical properties of the suture anchor (SA) versus transosseous tunnel (TO) techniques for quadriceps tendon (QT) repair. Methods: A systematic review was performed by searching PubMed, the Cochrane Library, and Embase using PRISMA guidelines to identify studies that evaluated the biomechanical properties of SA and TO techniques for repair of a ruptured QT. The search phrase used was "quadriceps tendon repair biomechanics". Evaluated properties included ultimate load to failure (N), displacement (mm), stiffness (N/mm), and mode of failure. Results: Five studies met inclusion criteria, including a total of 72 specimens undergoing QT repair via the SA technique and 42 via the TO technique. Three of 4 studies found QTs repaired with SA to have significantly less elongation upon initial cyclic loading when compared to QTs repaired with the TO technique (P < .05). Three of 5 studies found QTs repaired with SA to have significantly less elongation upon final cyclic loading when compared to QTs repaired with the TO technique (P < .05). The pooled analysis from 4 studies reporting on initial displacement showed a statistically significant difference in favor of the SA group compared to the TO group (P = .03). The pooled analysis from studies reporting on secondary displacement and ultimate load to failure showed no significant difference between the SA and TO groups (P > .05). The most common mode of failure in both groups was suture slippage. Conclusion: On the basis of the included cadaveric studies, QTs repaired via the SA technique have less initial displacement upon cyclic testing when compared to QTs repaired via the TO technique. However, final displacement and ultimate load to failure outcomes did not reveal differences between the two fixation strategies. Knot slippage remains a common failure method for both strategies.